Seri üretim montaj hatlarında ivme tabanlı montaj takip sisteminin tasarımı ve uygulaması - Ergen, Fahri Çağatay (My University, 2021)
Bu çalışmada montaj hatlarında yapılan hataları yerinde algılayıp düzeltebilmek için bileklik ve kullanıcılara uygun arayüz tasarlanmıştır. Montaj hattından hatalı geçen ürünlerin kalite kontrol aşamasına kadar hatalı devam etmemesi amaçlanmıştır. Çalışmada bileklik takılarak istasyondaki montaj parçalarının konumları ve ürün üzerindeki yerleri hazırlanan arayüze öğretilir. Operatör bilekliği takarak montaj üretimini gerçekleştirir. Hazırlanan arayüz operatörün hareket bilgilerini öğretilen verilerle ve sıralarıyla karşılaştırma yapar ve hata esnasında ekranda bilgilendirme yaparak yerinde düzeltme sağlar. Bu arayüz görsel tabanlı programlama ile hazırlanmıştır. Uygulama dört aşamadan oluşmaktadır.Birinci aşama, montaj sırası, içeriği ve planının oluşturulmasıdır. Bu aşama firmadaki yetkili kişilerce yapılır. Bilekliği yetkili bir kişi kullanarak montaj alma noktası ve bırakma noktalarını sırasıyla öğretir. Ayrıca öğretme esnasında montaj parçalarının fotoğraflarını ve bitmiş ürünün üç boyutlu fotoğrafını arayüze yüklemelidir.İkinci aşama, bu plandaki aşamaların operatöre gösterilmesidir. Programın içerisinde operatörün rahat anlaması amaçlandığından montaj parçalarının resimleri gösterilmektedir. Ayrıca montaj bittikten sonraki parçanın son hali üç boyutlu olarak gösterilebilmektedir. Bu bölüm OpenGL kütüphanesinin üst versiyonu olan ve bu tarz üç boyutlu gösterimler için oluşturulmuş olan OpenTK kütüphanesinden faydalanılarak yapılmıştır. Kullanıcıların burada gösterim yapabilmeleri için tasarımı bilgisayar destekli tasarım programları ile çizmiş olup *.stl formatında kayıt almış olması gerekir. Operatöre gösterimler sağlandıktan sonra üçüncü aşamaya geçilir.Üçüncü aşama, operatörün istasyondaki montajını bileklik kullanarak yapmasıdır. Tüm parçaların yerine montajı tamamlanır ve bu esnada parçaların verileri sensörler aracılığıyla okunup filtrelendirilerek hazırlanan arayüze gönderilir. Arayüz anlık olarak gelen verilerle önceden öğretilen verilerin karşılaştırmasını yapar. Hata mevcut ise operatörü uyarır. Aynı anda ekran üzerinde önceki parça, şimdiki parça ve sıradaki parça olarak fotoğraflarını göstererek operatörü bilgilendirir.Dördüncü ve son aşama ise üretim adetleri ve hata kontrolleridir. Montajda oluşan hata miktarları, montaj adetleri vb. bilgiler tarih ve saat etiketiyle beraber kayıt altına alınır. Bu kayıt istenilen zamanda yetkili kişilerce bilgisayardan usb ile alınabilir ya da mail olarak gönderimi sağlanabilir.

In this study, wristbands and user-friendly interface were designed to detect and correct errors in assembly lines. It is aimed those products that pass through the assembly line with errors will not continue with errors until the quality control stage. In the study, the positions of the assembly parts in the station and the places on the product are taught to the prepared interface by wearing a wristband. The operator wears the wristband and performs assembly production. The interface prepared compares the operator’s movement information with the taught date and their sequence, and provides on-site correction by informing the screen during the error. This interface is made in a visual based programming infrastructure. This application generally consists of four stages. The first step is to create the assembly sequence, content and plan. This stage is done by authorized persons in the company. Using the wristband by a competent person, it teaches the mounting point and drop points respectively. In addition, during the teaching, the photographs of the assembly parts and the three-dimensional photograph of the finished product should be uploaded to the interface. In this study, wristbands an user-friendly interface were designed to detech and correct errors in assembly lines on site. It is aimed those products that pass through the assembly line with errors will not continue with errors until the quality control stage. In the study, the positions of the assembly parts in the station and the places on the product are taugh to the prepared interface by wearing a wristband. The operator wears the wristband and performs assembly production. The interface prepared compares the operator’s movement information with the taught data and their sequence, and provides on-site correction by informing the screen during the error. This interface is made in a visual based programming infrastructure. This application generally consists of four stages. The second stage is to Show the stages in this plan to the operator. As the program is intended for the operator to understand easily pictures of the assembly parts are shown. In addition, the final state of the part after the assembly is completed can be shown in three dimensions. This section is made using the OpenTK library, which is an upper version of the OpenGL library and developed for this type of three-dimensional representation. In order for the users to be able to demonstrate here, the design must be drawn with computer-aided design programs and recoder in *.stl format. After the demonstrations are provided to the operator, the third stage is started. The third stage is for the operator to assemble at the station using a wristband. The assembly of all parts is completed, and in the meantime, the data of the parts are read and filtered through sensors and sent to the interface prepared. The interface compares instantly incoming data with previously taught data. If there is an error, it warns the operator. It informs the operator by showing the photos of the previous track, the current track and the next track on the screen at the same time. The fourth and final stage is production quantities and error checks. The amount of error in the assembly, the number of assemblies etc. information is recorded with date and time tags. This record can be taken from the computer via usb or sent by e-mail by authorized persons at any time.
Keywords: Arayüz; Assembly; Bileklik Visual; Engineering; Mechatronics; Mekatronik; Montaj; Mühendislik; Open-TK; OpenTK; Wristband